EFFECT OF THE ADDITION OF ANDALIMAN (Zanthoxylum acanthopodium) ON SKIPJACK (Katsuwonus pelamis) FLOSS TO CONSUMER ACCEPTANCE - Denny Fajar Timotius Ginting; Tjipto Leksono; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis study aims to find out the effect of the addition of andaliman on skipjack fish floss to consumer acceptance and how much the best addition of andaliman on the skipjack fish floss received by consumers. The treatment consists of A0 (without the addition of andaliman), A1 (addition of andaliman 2%), A2 (addition of andaliman 4%), A3 (addition of andaliman 6%). The parameters of the observed analysis are hedonic tests (color, aroma, taste and texture) and chemical analysis (water, protein, fat and ash). The addition of 6% andaliman (A3) is the best treatment that panelists like as much as 80 panelists (100%) with characteristics appereance dark brown , aroma of andaliman, specific spicy taste typical of andaliman and fish flesh taste, slightly fibrous texture.with water content of 6.04%, protein content of 25.55%, fat content of 16.69% and ash content of 6.02%.Keyword : Skipjack, andaliman, floss